In vitro kinetic release study of ketoprofen enantiomers from alginate metal complexes - Ghaidaa Alkhayer; Hussein Khudr; Yahia Koudsi (SpringerOpen, 2021)
Abstract Background To explore the release behavior of ketoprofen enantiomers from alginate-metal-complexes. Five mathematical models of drug release kinetics were investigated. Results Beads of alginate-metal complexes, loaded with racemic ketoprofen, were prepared by the ionotropic method. Divalent (Ca, Ba, Zn) and trivalent (Fe, Al) metals were used in the preparation of single-metal and mixed-metal alginate complexes. In vitro release experiments were carried out in an aqueous phosphate buffer medium at pH = 7.4. The concentrations of ketoprofen released enantiomers were determined using chiral HPLC technique. The obtained data were used to simulate the release kinetic of ketoprofen enantiomers using various mathematical models. The Korsmeyer-Peppas model was the best fit for Ca, Al, and Fe beads. Moreover, alginate-iron beads tend to release the drug faster than all other cases. In contrast, the drug release for alginate-barium complex was the slowest. The presence of barium in alginate mixed-metal complexes reduced ketoprofen release in the case of Fe and Zn, while it increased the release in the case of Al complex. Conclusion In all the studied cases, ketoprofen showed very slow release for both enantiomers over a period exceeded 5 h (10 days in some cases). The release rate modification is possible using different multivalent metals, and it is also feasible by using two different metals for congealing either consecutively or simultaneously.